the Merangkaikan Diri Di Padang Pastoral Digital: Kaum Muda Berkatakese Di Tengah Tantangan Hidup Menggereja - Damianus Suryo Pranoto; Oktovianus Son (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
Digital technology has brought a significant impact to the way young people interact and develop their identities. In this context, young people's digital pastoral care is often faced with challenges that can affect identity and behavior, can have both negative and positive impacts. Digital technology can be a means to help someone in being creative or developing, especially in pastoral care or proclaiming faith. The method used was qualitative by conducting interviews to investigate the views of Catholic youth on the use of digital technology in a religious context. The result is that when young people immerse themselves in the digital world, it becomes a tangible manifestation of how spirituality can synergize with technology, forming an inclusive platform where faith and daily life complement each other.